(untitled) (International journal of medical sciences, 2026)
This article analyzes the main etiological factors of dentofacial system anomalies and deformities, as well as modern preventive approaches to their prevention. Research findings indicate that hereditary, prenatal, and postnatal factors significantly influence the normal formation and development of the maxillofacial system. The necessity of implementing preventive measures at the primary, secondary, and tertiary levels is scientifically substantiated. Early diagnosis, elimination of harmful habits, preservation of primary teeth, and the application of interceptive orthodontic treatment methods contribute to preventing the development of complex orthodontic pathologies. A comprehensive and stage-by-stage preventive approach plays a crucial role in reducing the prevalence of dentofacial deformities among children and adolescents.